The Hsp90 Inhibitor, Monorden, Is a Promising Lead Compound for the Development of Novel Fungicides - Nguyen, Hang T. T.; Choi, Soyoung; Kim, Soonok; Lee, Ju-Hee; Park, Ae Ran; Yu, Nan Hee; Yoon, Hyeokjun; Bae, Chang-Hwan; Yeo, Joo Hong; Choi, Gyung Ja; Son, Hokyoung; Kim, Jin-Cheol (Frontiers in Plant Science, 2020)
Endophytic fungi are great resources for the identification of useful natural products such as antimicrobial agents. In this study, we performed the antifungal screening of various plant endophytic fungi against the dollar spot pathogen Sclerotinia homoeocarpa and finally selected Humicola sp. JS-0112 as a potential biocontrol agent. The bioactive compound produced by the strain JS-0112 was identified as monorden known as an inhibitor of heat shock protein 90 (Hsp90). Monorden exhibited strong antagonistic activity against most tested plant pathogenic fungi particularly against tree pathogens and oomycetes with the minimum inhibitory concentration values less than 2.5 µg mL-1. Extensive in planta assays revealed that monorden effectively suppressed the development of several important plant diseases such as rice blast, rice sheath blight, wheat leaf rust, creeping bentgrass dollar spot, and cucumber damping-off. Especially, it showed much stronger disease control efficacy against cucumber damping-off than a synthetic fungicide chlorothalonil. Subsequent molecular genetic analysis of fission yeast and Fusarium graminearum suggested that Hsp90 is a major inhibitory target of monorden, and sequence variation among fungal Hsp90 is a determinant for the dissimilar monorden sensitivity of fungi. This is the first report dealing with the disease control efficacy and antifungal mechanism of monorden against fungal plant diseases and we believe that monorden can be used as a lead molecule for developing novel fungicides with new action mechanism for the control of plant diseases caused by fungi and oomycetes.